Commission on the Democratic Selection of Presidential Nominees - Harold Hughes::::::
This explanatory memorandum from the Commission on the Democratic Selection of Presidential Nominees supports a Rules Committee Minority Report proposing reforms to delegate selection for the 1972 Democratic National Convention. The proposal would require that all delegate selection processes be open to public participation within the convention year and prohibit use of the unit rule at any level. It argues that more than 600 delegates at the 1968 Convention were chosen through processes begun years earlier, before candidates and issues were known, limiting meaningful voter participation. While the Credentials Committee majority also calls for more democratic systems, this memorandum contends that its language is too vague and lacks enforceable standards. The minority proposal instead seeks clear, explicit minimum requirements to ensure transparency and avoid future disputes over delegate legitimacy.